2017
DOI: 10.1021/acsnano.7b03673
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy toward Dual-Scale-Controlled Metallic Micro–Nano Hybrid Structures with Ultralow Reflectance

Abstract: Functional metal surfaces with minimum optical reflection over a broadband spectrum have essential importance for optical and optoelectronic devices. However, the intrinsically large optical impedance mismatch between metals and the free space causes a huge obstacle in achieving such a purpose. We propose and experimentally demonstrate a general pulse injection controlled ultrafast laser direct writing strategy for fabricating highly effective antireflection structures on metal surfaces. The presented strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(75 citation statements)
references
References 31 publications
1
73
1
Order By: Relevance
“…These particles can also contribute to an increase in absorption. If the focal diameter is significantly larger than the path distance, random coral-like structures are formed [19,20].…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…These particles can also contribute to an increase in absorption. If the focal diameter is significantly larger than the path distance, random coral-like structures are formed [19,20].…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
“…The shape and dimension of the structures and in particular the depth have a great influence on the absorption properties of the resulting surface. It has already been shown that this effect is not limited to a discrete wavelength spectrum, but affects all wavelengths from ultraviolet (~250 nm) to the near infrared (~2500 nm) [19][20][21].…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
“…Several techniques for fabricating micro-or nanostructures have been proposed, such as chemical etching [17], coating [18], reactive ion etching [19], and pulsed laser processing [20,21]. The chemical etching method is one of the most widely used techniques; it uses chemical etchants to etch the surface of the materials to form a rough surface, but there is poor control over the shape of the structures.…”
Section: Of 11mentioning
confidence: 99%
“…Lee et al [19] reported a design strategy to achieve a robust platform for plasmonenhanced light harvesting using aluminum core-shell nanostructures, which resulted in a remarkable increase in photo-to-chemical conversion. Fan et al [20] demonstrated an ultrafast laser-processing strategy for fabricating highly effective antireflection micro-nano-structures on thick metal surfaces, and an average reflectance of 4.1%, 2.4%, and 3.2% in the broadband spectrum from ultraviolet to near-infrared on Cu, Ti, and W, respectively, surfaces were achieved. However, to our best knowledge, there is no research on using nanostructured material to improve the laser absorption in LDFs.…”
Section: Introductionmentioning
confidence: 99%